Analysis of diversity and functional traits of epiphytic lichens in Dagestan forests of different formations - A. B. Ismailov (Юг России: экология, развитие)
Aim. The structure of forest communities changes along the altitude gradient, which determines the composition of epiphytic lichens. The aim of the study is to compare the species composition and functional characteristics of epiphytic lichens in Dagestan forests of different formations to identify key differences in the lichen flora.Material and Methods. Data on diversity and structure of 334 species of epiphytic lichens revealed during in field work from 2015 to 2019 were used as material for the work. Statistical analysis and data visualization were performed in Statistica 13.3 and PAST 4.0.Results. The highest number of epiphytic lichens was revealed in forests with complex tree structure with the participation of pine. A decrease of specific species and genera was noted with altitude increase. Cluster analysis of species, genera, reproductive strategies and growth forms showed the proximity of mountain forests (Pineta kochiana and Fageta orientalis) and their distance from lowland forests (Carpineta betulus). The percent  of  species  forming  vegetative  diaspores  increases  in mountain cluster forests. The "photobiont" indicator is clearer separated of studied formations. The greatest contribution to the division of the total sample is caused by difference in altitude, grouping the samples into mountainous and lowland.Conclusion. The differences in lichens species composition are results not only of diversity of the components which form the structure of the forest community,  but  also  of  specific  microclimatic  conditions  which  change with altitude, as well as the degree of anthropogenic disturbance.